2017
DOI: 10.1007/s11356-017-0395-2
|View full text |Cite
|
Sign up to set email alerts
|

Frog (Pelophylax bergeri, Günther 1986) endocrine disruption assessment: characterization and role of skin poly(ADP-ribose) polymerases

Abstract: Model of the our research was the adult male amphibian anura, Pelophylax bergeri, poikilotherm species not considered threatened by the IUCN, sampled in representative sites at different degree. In the first phase, a biochemical characterization of the ADP-ribosylation on the skin of barcoded amphibian anura collected from Matese Lake (clean reference site in CE, Italy) was carried out. Two PARP isoforms were evidence: the first of 66 kDa is localized into nucleus and activated by DNA damage; the second of 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…They usually use their own skin as a secondary respiratory surface, which is permeable to endogenous and exogenous substances whose potential harmful effects are contrasted by the combined action of keratins. This factor makes them particularly suitable as a biosentinel [122][123][124].…”
Section: Amphibiamentioning
confidence: 99%
“…They usually use their own skin as a secondary respiratory surface, which is permeable to endogenous and exogenous substances whose potential harmful effects are contrasted by the combined action of keratins. This factor makes them particularly suitable as a biosentinel [122][123][124].…”
Section: Amphibiamentioning
confidence: 99%
“…Previous reports have suggested that steroid hormones, receptors and oxidative stresses might influence various aspects of reproduction. Further studies on light and temperature variations by antioxidants using enzymatic assay (Guerriero et al 2003), chromatography (Guerriero et al 2004) and expression analysis of steroid receptors (Guerriero et al 2005(Guerriero et al , 2009(Guerriero et al , 2017a and dosing free radicals with real-time quantitative polymerase chain reaction (PCR) (Guerriero et al 2017b) are needed in the future.…”
Section: 2mentioning
confidence: 99%
“…Similarly, Vašeková (2017) shows a significant influence of temperature on the length of metamorphosis and the sex of Xenopus laevis. Other authors observed other factors in their study, such as reproductive biomarkers, free radicals by electron spin resonance (Guerriero et al 2017a), antioxidants using enzymatic assay (Guerriero et al 2003), chromatography (Guerriero et al 2004), and expression of steroid receptors (Guerriero et al 2005(Guerriero et al , 2009(Guerriero et al , 2017b, in parallel to the approach already used.…”
Section: Discussionmentioning
confidence: 97%